Psicoanálisis, política y cultura en la Argentina de los sesenta - Pablo Ponza (Nuevo mundo - Mundos Nuevos, 2011)
This paper attempts to analyse the way in which psychology emerged and became firmly established as a professional activity in Argentina in the decade called the sixties (1955 - 1971) and describe how its development and establishment as an independent discipline were influenced by the changing political and cultural conditions of the country in that period. For this purpose, the article places psychology among the modern social sciences that were involved in the project for modernization of university after Peron’s government, along with the emergence of a flourishing group of middle-class intellectuals and the strong development of the publishing industry at that time. All these events are placed and interpreted within a context of high instability and gradual spread of radical ideologies. This radicalisation was observed not only in the politicisation of culture, thought and art, but also to a great extent among psychologists.